A review of bevacizumab and its use in colorectal cancer - Tonon, Lenita Maria (2007)
Objective: To perform a systematic review of the use of bevacizumab in the treatment of metastatic colorectal cancer. Methodology: The current study is a literature review based on data from LILACS, PUBMED, Journal of Clinical Oncology (JCO), and Micromedex. Results: 7 articles were identified, of which 57.10% (n=4) were published in JCO. For the respective populations studied in these articles, median age varied from 60 to 67 years and the sample size varied from 19 to 411 subjects. The most frequent chemotherapy regimens were 5-fluorouracil/leucovorin (5-FU/LV) and 5-FU/LV/irinotecan (IFL), both with bevacizumab. Median survival ranged from 6 to 21.5 months, and median progression-free survival ranged from 4 to 10.6 months in the groups that received bevacizumab. Adverse events (grades 3 and 4) were more frequent in the bevacizumab/IFL group. Conclusion: Few articles have been published on bevacizumab and colorectal cancer. Bevacizumab has been approved by the National Health Surveillance Agency (ANVISA) for use in Brazil but is not available on the market. As a result, there are no Brazilian articles on it. Therapy using bevacizumab offers benefits to the patients. However, it is important to remember that although associated adverse events are rare, they can have an important clinical and economic impact.